2021
DOI: 10.1039/d0ra09302e
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of emulsification behaviour of pea and faba bean protein concentrates and isolates from structure–functionality analysis

Abstract: The effects of different extraction methods on the structure–functionality and emulsification behaviour of pea and faba bean proteins were studied, and a regression model was developed to predict emulsion characteristics based on protein properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 64 publications
7
13
0
Order By: Relevance
“…QSAR modeling aims to develop quantitative expressions that correlate the molecular features of proteins to their functional properties [ 85 ]. Models have been developed using a wide range of statistical modeling techniques, ranging from regression methods (such as the partial least square and response surface methods) [ 86 , 87 , 88 ] to modern machine learning techniques (such as artificial neural networks) [ 89 , 90 , 91 ].…”
Section: Prediction Of Plant Protein Functional Propertiesmentioning
confidence: 99%
“…QSAR modeling aims to develop quantitative expressions that correlate the molecular features of proteins to their functional properties [ 85 ]. Models have been developed using a wide range of statistical modeling techniques, ranging from regression methods (such as the partial least square and response surface methods) [ 86 , 87 , 88 ] to modern machine learning techniques (such as artificial neural networks) [ 89 , 90 , 91 ].…”
Section: Prediction Of Plant Protein Functional Propertiesmentioning
confidence: 99%
“…Therefore, plant proteins are gaining more interest, across the globe, due to their wide range of applications in plant‐based food systems. In the food industry, plant proteins are used to replace animal proteins to meet consumer demand, while improving nutritional values and maintaining similar functionality and sensory characteristics ( i.e ., texture, flavor, and color) (Keivaninahr et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…FBPIs were commonly extracted via the wet methods (alkaline extraction and isoelectric precipitation) followed by lyophilization or spray drying, which might change the native protein structure and influence the functional properties. Recently, Keivaninahr et al (2021) compared the emulsifying properties of faba bean protein extracted by the conventional wet method and by air classification. They found that the latter method produced proteins with lower protein content but higher solubility; the proteins obtained by air classification also produced emulsions with better or comparable characters in terms of particle size, zeta potential, and microstructure.…”
Section: Enzymatic Modificationsmentioning
confidence: 99%